Analysis of Local Electoral Governance under Electoral Integrity Perspective in Yogyakarta City 2017 - Riska Sarofah; Titin Purwaningsih; Nurhakim Nurhakim (Journal of Government and Civil Society, 2018)
The characteristic of a democratic country is implementation of election. In Indonesia it has include in national and local levels. Local elections held simultaneously in 2015, 2017 and 2018. One of the city conducting the election is Yogyakarta City. In the specifically this research explain about electoral governance in electoral integrity perspective. All stages of election which consists of pre-election, election period and post-election. This research use qualitative research method through interview and documentation. The results of this study indicated that electoral governance in Yogyakarta City has integrity in accordance with the principles of electoral integrity applied in the stages of election implementation include pre-election, election process and post-election. In this research are not use all of the indicators to analyse the stages of election. This is because adjusted with the findings of research with information obtained through several sources. The first, at the planning and program, the indicators analyse include the implementation of democratic principles, transparency and accountability. The second, socialization and voter information, indicators analyse include the implementation of democratic principles, transparency and professionalism. The third, campaigns, indicators analyse include transparency, accountability, code of ethics and supervision. The fourth, voting and vote counting, the indicators analyse include democratic principle, professionalism, institutional safeguards and supervision. The fifth, the resolution of election disputes, indicators analyse are ethical codes and accountability.